2015
DOI: 10.1038/srep11648
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of haemagglutinin (H) gene in measles virus

Abstract: We studied the molecular evolution of the haemagglutinin (H) gene (full length) in all genotypes (24 genotypes, 297 strains) of measles virus (MeV). The gene’s evolutionary timescale was estimated by the Bayesian Markov chain Monte Carlo (MCMC) method. We also analysed positive selection sites. The MCMC tree indicated that the MeV H gene diverged from the rinderpest virus (same genus) about 250 years ago and that 24 MeV genotypes formed 3 lineages dating back to a 1915 ancestor (95% highest posterior density [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…The model with the lowest AICM value was selected to be the best-fit model in each sequence dataset and used for analysis (Kimura et al, 2015;Nagasawa et al, 2015) (Supplementary Table 1).…”
Section: Carlo (Mcmc) and Maximum Likelihood (Ml) Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model with the lowest AICM value was selected to be the best-fit model in each sequence dataset and used for analysis (Kimura et al, 2015;Nagasawa et al, 2015) (Supplementary Table 1).…”
Section: Carlo (Mcmc) and Maximum Likelihood (Ml) Methodsmentioning
confidence: 99%
“…To assess the time course trend of effective population size (EPS) of overall RSV-A strains circulating in central Vietnam during the investigation period, Bayesian Skyline Plot (BSP) was constructed using BEAST ver.1.8.0 as previously described (Drummond and Rambaut, 2007;Kimura et al, 2015;Nagasawa et al, 2015). KAKUSAN4 was used for the selection of best-fit nucleotide substitution model.…”
Section: Bayesian Skyline Plot (Bsp) Analysismentioning
confidence: 99%
“…To date, 24 MeV genotypes are recognized with preferential geographic circulation. A Bayesian skyline plot analysis suggested that prevalent genotypes such as genotype D4 are more adaptive to humans (61). The fact that most of the subgenotype D4.1 sequences that we retrieved from GenBank were derived from Kenya and Ethiopia, whereas the MAb-resistant subgenotype D4.2 MeV sequences were derived predominantly from France and Great Britain, might suggest that an intermediary level of vaccine coverage provides an environment more prone to adaptive mutations.…”
Section: New D4 Subgenotype Of Measles Virusmentioning
confidence: 99%
“…However, the fact linked with viruses and hosts which caused the divergence or convergence in the phylogenetic trees remained unclear. Two studies showed that the rate of variation of PPRV HN gene is higher than that of the MV H gene (66,81). In addition, the variation of PPRVHN gene is faster than that of the genome, which may be the result of the ability of PPRV HN to adapt to large host immune pressure.…”
Section: Mechanisms For Peste Des Petits Ruminants Virus Interspeciesmentioning
confidence: 99%